Alpha-alpha scattering in the range 36.8 to 42.3 Mev - Conzett, Homer; Igo, George; Shaw, Harlan; Slobodorian, Rodolfo J. (American Physical Society, 1960)
Fil: Conzett, Homer George Department of Physics, Stanford University; Estados Unidos